Veränderungen der Berufsstruktur der Beschäftigung in Wien 2001-2012 - Mesch, Michael (Wirtschaft und Gesellschaft, 2014)
Between 2001 and 2012 the occupational structure of the labor force in Vienna shifted significantly towards high-skilled white-collar occupations. Professionals, technicians and associated professionals, and managers already constitute half of the labor force at the workplace Vienna. The very strong employment shift towards professionals is interpreted as unambiguous evidence of structural change in the direction of knowledge-intensive and human capital-intensive service activities. Applying shift-share-analysis it is shown that within industry occupational shifts as well as between industries shifts of roughly the same magnitude contributed to the aggregate changes in the occupation-industry-matrix of the labor force. The observed shifts towards high-skilled white-collar occupations and mid-skilled, interactive white-collar occupations and away from mid-skilled white-collar occupations carrying out routine clerical tasks as well as away from mid-skilled and low-skilled blue-collar occupations is consistent with the refined theory of technical progress provided by the "routinization"-hypothesis advanced by Autor et al. (2003): computers and other IT equipment complement both high-skilled non-routine analytical tasks and mid-skilled nonroutine interactive tasks, but substitute for mid-skilled routine cognitive tasks and for midskilled and low-skilled routine manual tasks.